Conflict resolution interventions in the conflict cycle - Sousa, Ricardo Real P. de (2021)
The objective of this article is to describe the Conflict Resolution interventions used throughout the conflict cycle. The article first presents five levels of conflict intensity of the conflict cycle, namely the levels of Stable Peace, Unstable Peace, Conflict, Crisis, and War. Each level of conflict intensity is characterized by analyzing the variables of Galtung's conflict triangle (behavior, attitudes, and goals), actors' perceptions (friend, rival, and enemy), and the dominant strategy of interaction between actors (positive-sum, compromise, zero-sum, and negative-sum). Each level is illustrated with typical events associated with civil wars and wars between states and proposes threshold events of a possible change in the level of conflict intensity. The article then presents a set of Conflict Resolution approaches that can be carried out in each of the conflict intensity levels of the escalation and de escalation periods of the conflict cycle. Conflict Resolution is subdivided between interventions whose main objective is to contain violent conflict, here called Conflict Management, and interventions with a main objective of solving political problems, which can be Conflict Prevention, if they occur in the period of conflict escalation, or Conflict Termination, if they occur in the period of conflict de escalation. In Conflict Management we identify the interventions of: Crisis Management; Unilateral and Joint Internal Management; External Management in the form of Peacemaking or Peace Enforcement, and Traditional Peacekeeping. In Conflict Prevention we identify Structural and Direct Prevention. In Conflict Termination we identify Multidimensional Peacekeeping, Peacebuilding and Peace Consolidation (associated to Conflict Transformation). Additionally, we present two alternative approaches, Cosmopolitan Peace and Critical Approaches.